The diet of open-habitat chimpanzees (Pan troglodytes schweinfurthii) in the Issa valley, western Tanzania. Issue 112 (November 2017) - Piel, Alex K.; Strampelli, Paolo; Greathead, Emily; Hernandez-Aguilar, R. Adriana; Moore, Jim; Stewart, Fiona A.
Abstract: Comparative data on the diets of extant primates inform hypotheses about hominin resource use. Historically, data describing chimpanzee diets stem primarily from forest-dwelling communities, and we lack comparative data from chimpanzees that live in mosaic habitats that more closely resemble those reconstructed for Plio-Pleistocene hominins. We present data on the diet of a partially-habituated community of open habitat chimpanzees ( Pan troglodytes schweinfurthii ) from the Issa valley, western Tanzania, collected over a four-year period. Based mostly on macroscopic faecal analysis, Issa chimpanzees consumed a minimum of 69 plant species. There was no relationship between plant consumption and either fruit availability or feeding tree density; the most frequently consumed plant species were found in riverine forests, with woodland species consumed more frequently during the late dry season. We conclude by contextualising these findings with those of other open-habitat chimpanzee sites, and also by discussing how our results contribute towards reconstructions of early hominin exploitation of mosaic landscapes.